Consumer Protection Awareness in Online Shopping Among Senior High School Students in Muaro Bungo - Muskibah, Muskibah; Hasan, Umar; Suhermi, Suhermi; Sasmiar, Sasmiar; Pahlefi, Pahlefi (LPPM Universitas Jambi, 2024)
This community service initiative aims to enhance public legal literacy concerning consumer rights and obligations in the context of online shopping, while also fostering greater awareness and caution regarding potential criminal acts in digital transactions. Additionally, the program seeks to improve public understanding of mechanisms for resolving disputes arising from online purchases. The activities were conducted at Senior High School 2 Muaro Bungo, Muaro Bungo Regency, utilizing both virtual and in-person formats, including lectures and interactive discussions. Findings from the implementation indicate a significant improvement in participants’ comprehension of consumer protection issues. The program, titled “Dissemination on Consumer Protection in Online Shopping for Students of Senior High School 2 Muaro Bungo,” demonstrated a marked increase in the participants’ ability to grasp and retain the information delivered. This improvement was observed through their growing familiarity with the principles of consumer protection, particularly within the realm of online shopping. In conclusion, continuous efforts are needed to promote legal education on digital consumer rights. The results show that this activity effectively raised participants’ legal awareness and provided them with practical knowledge about their rights, duties, and the proper procedures for resolving conflicts in online commerce.